Developing an online food composition database for an Indigenous population in south-western Uganda. Issue 9 (12th June 2021) - Scarpa, Giulia; Berrang-Ford, Lea; Bawajeeh, Areej O; Twesigomwe, Sabastian; Kakwangire, Paul; Peters, Remco; Beer, Sarah; Williams, Grace; Zavaleta-Cortijo, Carol; Namanya, Didacus B; Lwasa, Shuaib; Nowembabazi, Ester; et al.
Abstract: Objective: To develop an online food composition database of locally consumed foods among an Indigenous population in south-western Uganda. Design: Using a community-based approach and collaboration with local nutritionists, we collected a list of foods for inclusion in the database through focus group discussions, an individual dietary survey and markets and shops assessment. The food database was then created using seven steps: identification of foods for inclusion in the database; initial data cleaning and removal of duplicate items; linkage of foods to existing generic food composition tables; mapping and calculation of the nutrient content of recipes and foods; allocating portion sizes and accompanying foods; quality checks with local and international nutritionists; and translation into relevant local languages. Setting: Kanungu District, south-western Uganda. Participants: Seventy-four participants, 36 Indigenous Batwa and 38 Bakiga, were randomly selected and interviewed to inform the development of a food list prior the construction of the food database. Results: We developed an online food database for south-western Uganda including 148 commonly consumed foods complete with values for 120 micronutrients and macronutrients. This was for use with the online dietary assessment tool myfood24. Of the locally reported foods included, 56 % ( n 82 items) of the items were already available in the myfood24 database, while 25 % ( n 37 items) were found in existing Ugandan and Tanzanian food databases, 18 % ( n 27 items) came from generated recipes and 1 % ( n 2 items) from food packaging labels. Conclusion: Locally relevant food databases are sparse for African Indigenous communities. Here, we created a tool that can be used for assessing food intake and for tracking undernutrition among the communities living in Kanungu District. This will help to develop locally relevant food and nutrition policies.